Knowledge and Practices of Dentists Towards Patients on Antithrombotic Medication Therapy: A Cross-Sectional Survey - Erçal, Pınar; Tayşi, Ayşegül Erten; Şişmanoğlu, Soner (Cerrahpaşa Medical Journal, 2023)
Objective: The objective of the present study was to describe the knowledge, perception, and practices of general dentists and dentists with various specializations regarding the management of patients on antithrombotic drug therapy. Methods: A cross-sectional survey of dentists and specialists from different educational institutions and workplaces was conducted in Turkey between May 2022 and July 2022. The sample size comprised 153 subjects and participants completed an electronic questionnaire containing 24 questions. Descriptive statistical analyses were performed to evaluate data. Results: Most of the surveyed dentists were aware of acetylsalicylic acid (ASA) and warfarin, while the novel antithrombotic agents, apixaban and rivaroxaban were less known. Regarding the management of patients on novel oral antithrombotic medication during different dental procedures, there were no significant differences within groups according to clinical experience year (p=0.409), whereas, for patients on ASA, both years of experience and area of expertise affected the participant’s approach (p=0.001). Monitoring of patients before dental procedures regarding blood tests did not differ according to years of clinical experience or specialty (p=0.185, p=0.688). Most participants (92%) sought a physician’s opinion before invasive dental procedures regardless of the type of oral antithrombotic medication. Conclusion: Knowledge and dental management of patients on oral antithrombotic medications varied among dentists. Evident hesitancy towards treating such patients indicates a necessity for continuing education programs among dentists to provide better care for the patients without any fear of cardiovascular consequences.